MENGURANGI GAP PERGURUAN TINGGI DENGAN DUNIA KERJA: UPAYA PENINGKATAN KUALITAS SUMBERDAYA MANUSIA - fitri, agus zaenul (J-MPI (Jurnal Manajemen Pendidikan Islam), 2016)
The high capability for managing Higher Education (HE) is necessary which include adopting of modern management principles that focus on quality, continous improvement and customer satisfaction. Globalization era is competation era, so HE must based quality in any of its processed. The students of HE that still studying need a product of motivation and double communication that are; science, academic title, skill, experience, belief and good behaviour on the contex of balance. All of them need to work in workplace expected a better life in this world is systematic attempt to increase human resources quality. There are four points on education field, namely; average and opportunity of education, relevancy with development, quality and efficiency. Therefor HE needs to support a certain aim to increase their level lecturer qualification with next educational level or non-degree course in order to enhance a quality of human resources resulted automatically will support a quality of education at HE.Keywords:  Gap, Pendidikan, Dunia Kerja, SDM